2019
DOI: 10.3390/agronomy9120850
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Proximal and Distal Grains Within Spikelets in Relation to Yield and Yield Components in the Winter Wheat Production Region of China From 1948 to 2012

Abstract: Grain number and weight within a spikelet are major yield components which determine the grain yield in wheat. The objective of this study was to explore genetic gains in grain performance within wheat spikelets at the individual grain level and its effect on grain yield and evaluate genetic progress in stem internode length and other yield-related traits. We conducted field experiments across three growing seasons in the western Yellow and Huai Valley of China; incorporating 17 bread wheat cultivars released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Both the processes described above, would lead to a higher proportion of small grains and so will be referred to below as 'populational' effects. The important roles of these populational effects on the trade-off between GNM2 and AGW is supported by a large number of studies (Acreche and Slafer, 2006;Chen et al, 2019;Feng et al, 2019;Ferrante et al, 2017;García et al, 2013;Li et al, 2016;Miralles and Slafer, 1995b;Quintero et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Both the processes described above, would lead to a higher proportion of small grains and so will be referred to below as 'populational' effects. The important roles of these populational effects on the trade-off between GNM2 and AGW is supported by a large number of studies (Acreche and Slafer, 2006;Chen et al, 2019;Feng et al, 2019;Ferrante et al, 2017;García et al, 2013;Li et al, 2016;Miralles and Slafer, 1995b;Quintero et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Most studies comparing wheat cultivars and showing differences in grain number and AGW have focused on the dichotomy between old cultivars and new ones, or between tall cultivars and semi-dwarf ones (Chen et al, 2019;Ferrante et al, 2017;Miralles and Slafer, 1995b), or they have explored cultivars showing wide-ranging yield potentials (e.g., Peltonen-Sainio et al, 2007;Quintero et al, 2018). All these studies, together with an abundance of studies that have focused on yield responses to different management practices (e.g., Acreche and Slafer, 2006;Feng et al, 2019;Fischer, 1993;Li et al, 2016) have concluded that yield variations are mainly related to variations in GNM2 (e.g., Slafer et al, 2014 and references therein). Given the negative relationship that commonly exists between GNM2 and AGW (Slafer et al, 2014;Slafer and Savin, 1994), studies that rely on a high variability in GNM2, only highlight the dominant effect of GNM2 on AGW.…”
Section: Relevance Of the Selected Cultivars To Exploring The Grain N...mentioning
confidence: 99%
See 2 more Smart Citations
“…Under normal conditions, the grain formation rate per average per spikelet of the wheat spike is around 2.7, and it is well known that the sterility rate in the third florets of the wheat spike is about 30% [61]. One of the most important reasons why the WW genotypes tested had low GY was sterility in the spike (SS).…”
Section: Heat and Drought Tolerancementioning
confidence: 99%